Multiple Voices and Multiple Senses of Ethnic Belonging: a study of Kiriris and Payayás indigenous remnants - Souza, Leila Damiana Almeida dos Santos; Souza, Kleber Peixoto de (Educação, Escola & Sociedade, 2021)
In this article we present epistemological aspects that contribute to the analysis of the constitution of the ethnic identity of one of the human groups that make up the diversity of the remnants of the Kiriris and Payayás indigenous peoples, in the district of Missão do Sahy, in Senhor do Bonfim, Bahia. Methodologically, we use oral history to approach the constitutive processes of the indigenous remnants and, consequently, contribute to the cultural strengthening of the ancestors of the Kiriris and Payayás who reside there. The results show us that, through a dialogical action, it was possible to contribute to the process of building the ethnic identity of the subjects involved. Keywords: Dialogy. Ethnic Identity. Indigenous remnants.